2014
DOI: 10.1089/aid.2013.0271
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Drug Resistance-Associated Mutations in Human Immunodeficiency Virus Type 1 Integrase Derived from Drug-Naive Individuals in Surabaya, Indonesia

Abstract: Although human immunodeficiency virus type 1 (HIV-1) infection causes serious health problems in Indonesia, information in regard to drug resistance is limited. We performed a genotypic study on HIV-1 integrase derived from drug-naive individuals in Surabaya, Indonesia. Sequencing analysis revealed that no primary mutations associated with drug resistance to integrase inhibitors were detected; however, secondary mutations, V72I, L74I/M, V165I, V201I, I203M, and S230N, were detected in more than 5% of samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
(22 reference statements)
3
11
0
Order By: Relevance
“…The fact that only 0.6% of samples analyzed had INSTIs major RAMs suggests that there will be a lesser likelihood of resistance to INSTIs in Cameroon and that INSTIs will be effective for HIV-infected Cameroonians. Similar trends were observed in other countries in Africa [13,34,[43][44][45], Asia [46][47][48][49][50][51], Europe [52][53][54], and South America [55] where studies showed a low frequency of INSTIs major RAMs.…”
Section: Discussionsupporting
confidence: 81%
“…The fact that only 0.6% of samples analyzed had INSTIs major RAMs suggests that there will be a lesser likelihood of resistance to INSTIs in Cameroon and that INSTIs will be effective for HIV-infected Cameroonians. Similar trends were observed in other countries in Africa [13,34,[43][44][45], Asia [46][47][48][49][50][51], Europe [52][53][54], and South America [55] where studies showed a low frequency of INSTIs major RAMs.…”
Section: Discussionsupporting
confidence: 81%
“…The mutations, M184V and K103N are commonly detected as multi-drug resistance mutations leading to the virological failure of a first-line NRTIs-and NNRTI-based regimens [16,28]. The appearance pattern of these drug resistance mutations was similar with those in previous studies in Indonesia, Malaysia, Taiwan, Turkey, and USA [17,[18][19][20][21][22][23][24][25][26][27][28][29][30][31]. M184V is a common mutation in treated populations; however, it is very rare among…”
Section: Discussionsupporting
confidence: 77%
“…Minor mutations have been detected in PR genes of non-B subtypes, including CRF01_AE, as natural polymorphisms [14]. Drug resistance-associated minor mutations in PR genes have also been reported in other studies in Indonesia [11,17,18].…”
Section: Dmentioning
confidence: 62%
See 1 more Smart Citation
“…The 5′ terminal half of the HIV-1 genome (former fragment) and 3′ terminal half of the genome (latter fragment) were individually amplified by nested PCR using the Expand Long Template PCR System (Roche Diagnostics). Regarding the former fragment, first-round PCR was performed with the msf12b 24,25 and DRIN02 primers 26 and was followed by second-round nested PCR with the f2nst 24 and DRIN04 primers 26 . The conditions for PCR were as follows: in first PCR, initial denaturation at 94 °C for 2 minutes followed by 10 cycles of 94 °C for 10 seconds, 55 °C for 30 seconds, and 68 °C for 4 minutes, and 25 cycles of 94 °C for 15 seconds, 55 °C for 30 seconds, and 68 °C for 4 minutes and 20 seconds, and final extension at 68 °C for 7 minutes.…”
Section: Methodsmentioning
confidence: 99%